Diseño de un plan de marketing turístico para la parroquia de Nayón, ubicada en el Distrito Metropolitano de Quito - Chanchay Luguaña, Hilda Susana (2015)
Nayón was created in 1935, today is one of the most representative of the Metropolitan District of Quito as a result of the high concentration of growing ornamental plants. Since this sector grow and sell many of the plants that adorn the houses of the Quito population reason that have led to the nickname "The Garden of Quito." Currently despite being heavily visited there is an attractive tourist offer, since the proposals have not reached a level of planning, implementation and proper dissemination therefore do not represent a tangible social benefits for the population, hence there is no evidence a tourist solid proposal in the Parish. With this investigation it was determined that the parish has tourism potential that has not been enhanced, so we have developed a marketing plan to promote tourism development in this sector and attract new visitors. In this research, the implementation of various activities are recommended, the same as those based on surveys and interviews, as well as in the literature to make a tourist destination Nayón recommended.